Activation of β‐catenin by TGF‐β1 promotes ligament‐fibroblastic differentiation and inhibits cementoblastic differentiation of human periodontal ligament cells. (23rd September 2020) - Lim, Jong‐Chan; Bae, Sang‐Hoon; Lee, Gyutae; Ryu, Chun Jeih; Jang, Young‐Joo
Abstract: TGF‐β and Wnt/β‐catenin signaling pathways are known to be essential for the development of periodontal tissue. In this study, we examined the crosstalk between TGF‐β and Wnt/β‐catenin signaling in ligament‐fibroblastic differentiation of human periodontal ligament cells (hPDLCs). TGF‐β1 treatment significantly increased the expression of ligament‐fibroblastic markers, but such expression was preventing by treatment with SB431542, a TGF‐β type I receptor inhibitor. As well as phosphorylation of Smad3, TGF‐β1 increased β‐catenin activation. The depletion of β‐catenin reduced the expression of ligament‐fibroblastic markers, suggesting that β‐catenin is essential for ligament differentiation. The effect of TGF‐β1 on β‐catenin activation did not seem to be much correlated with Wnt stimuli, but endogenous DKK1 was suppressed by TGF‐β1, indicating that β‐catenin activation could be increased much more by TGF‐β1. In addition to DKK1 suppression, Smad3 phosphorylation by TGF‐β1 facilitated the nuclear translocation of cytoplasmic β‐catenin. In contrast to ligament‐fibroblastic differentiation, inhibition of TGF‐β1 signaling was needed for cementoblastic differentiation of hPDLCs. BMP7 treatment accompanied by inhibition of TGF‐β1 signaling had a synergistic effect on cementoblastic differentiation. In conclusion, β‐catenin activation by TGF‐β1 caused ligament‐fibroblastic differentiation of hPDLCs, and the presence of TGF‐β1 stimuli basically determined whether hPDLCs are differentiated into ligament progenitor or cementoblasts. Abstract : Through an interrelation between TGF‐β1 and Wnt signaling, ligament‐fibroblastic differentiation of adult periodontal ligament stem cells (hPDLCs) can be induced. Phosphorylated Smad3 by TGF‐β1 interacts with the active β‐catenin and moves into nucleus, followed by expression of ligament‐fibroblastic genes. DKK1 inhibition by TGF‐β1 is also essential for β‐catenin activation. Complete blocking of TGF‐β1 signaling is essential for cementogenesis of hPDLCs.